Evaluation studies on effects of pectin with different concentrations on the pasting, rheological and digestibility properties of corn starch. (15th February 2019) - Ma, Yong-Shuai; Pan, Yi; Xie, Qiu-Tao; Li, Xiao-Min; Zhang, Bao; Chen, Han-Qing
Highlights: The high concentrations of PE (2.0%, 5.0% and 10.0%) increased the peak viscosity. The CS-PE mixtures exhibited a pseudoplastic and shear-thinning behavior. Pectin promoted a remarkable reduction in the fraction of RDS. The PE decreased the hydrolysis rate of CS with lower values of C∞ and k. Abstract: In this paper, the effects of pectin (PE) with different concentrations on the pasting, rheological and digestibility properties of corn starch (CS) were evaluated. The Rapid Visco-Analyzer results showed that the peak viscosity was decreased with the concentrations of PE (0.5% and 1.0%) and then increased when the concentration of PE exceeded 2.0%. PE resulted in lower breakdown and setback values of CS. Rheological results revealed that the CS and CS-PE mixtures exhibited a pseudoplastic and shear-thinning behavior. The storage modulus (G′) and loss modulus (G″) of CS were increased with increasing PE concentrations from 2.0% to 10.0%. PE resulted in a decrease in the starch susceptibility to α-amylase and promoted a remarkable reduction (P < 0.05) in the fraction of rapidly digested starch. The hydrolysis kinetic analysis suggested a decelerating effect of pectin on the hydrolysis rate of CS with lower values of equilibrium hydrolysis percentage (C∞ ) and kinetic constant (k).